TEORI PRODUKSI PENDEKATAN ISOCOST – ISOQUANT (LONGRUN) - Samuel Revaldo Jeverson Siboro; Roma Uli Maria Situmeang; Olive Katrina Joyanka Sihombing; Josua Pane; Fredy Syahputra (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2025)
This study aims to analyze production theory in the long run using the isocost and isoquant approach as graphical and analytical tools. In long-run production theory, all inputs are considered variable, allowing firms to adjust the combination of production factors to achieve maximum efficiency. The isoquant approach illustrates various combinations of inputs that produce the same level of output, while the isocost line represents combinations of inputs with the same total cost. The optimal production point is reached when the isoquant curve is tangent to the isocost line, indicating the input combination that minimizes cost for a given level of output. This study highlights that understanding these concepts is crucial for production managers and decision-makers in designing cost-efficiency strategies and improving productivity. Through this approach, firms can achieve an efficient and sustainable production equilibrium in the long run.